Formation and reduction of 5-hydroxymethylfurfural during deep-fat frying of bananas - Kavousi, Parviz (2014)
5-hydroxymethylfurfural (HMF) is a heat-induced furanic compound that is formed through Maillard reaction or direct dehydration of hexoses under acidic conditions in carbohydrate-containing food products. Human exposure to HMF mainly takes place through diet. 5-sulfoxymethylfurfural (SMF), as a metabolite of HMF, can react with DNA and other macromolecules, and acts as a toxic and mutagenic compound. This gives rise to concern for reducing the HMF content in thermally processed foods especially fried food products. Up to now the formation and reduction of HMF during deep-fat frying is not clear. This study is conducted to investigate the formation and reduction of HMF during deep-fat frying of banana. The effects of amino acids (15 amino acids) and sugars (fructose, glucose and sucrose) as precursors on the formation and reduction of HMF are evaluated in model systems. The HMF is extracted and separated using an optimized extraction procedure and a validated HPLC method. The results reveal that glutamine, glutamic and aspartic acids enhance the formation of HMF. Conversly, lysine, arginine and histidine reduce the HMF content to non-detectable level. The HMF content in control samples containing glucose, fructose or sucrose alone was 167.99, 232.79 and 18.54 m/kg, respectively. While, in binary mixtures of these sugars with glutamine, aspartic acid and glutamic acid, the formation of HMF was significantly (P<0.05) increased and reached to 1084.60, 2020.30 and 3816.90 mg/kg, 1115.40, 751.00 and 1232.60 and 1653.30, 1556.60 and 3132.60 mg/kg, respectively (P< 0.05). The formation of HMF is significantly (P<0.05) reduced by 73.23% and 90.71% in Abu variety and 76.33% and 82.84% in Tanduk variety, respectively after pre-soaking of bananas in water containing lysine or arginine (0.06 M) for 2 h compared to control samples. The current study reveals that the food compositions have had a more significant effect than frying oil in the formation of HMF (P<0.05). The effect of frying time on HMF formation is significantly (P< 0.05) higher than frying temperature. Microwave frying causes the higher HMF formation than conventional deep-fat frying and boiling process. The HMF content in bananas after 6 min cooking was 2168.02, 31.92 and 0.17 mg/kg, respectively. In addition, the effects of the banana variety (7 varieties), ripening stage (ripe and unripe), surface area-to-volume ratio and blanching process on the reduction of HMF are studied. The results show that HMF forms at significantly lower amount in unripe fruits (P<0.05). HMF content in fried Tanduk is lower than Mas, Abu, Berangan, Raja, Ambon and Awak varieties. Moreover, HMF formation is significantly (P<0.05) increased from 26.81 to 124.83 mg/kg by increasing the surface area-to-volume ration from 0.02 mm-1 to 0.80 mm-1(P<0.05) The results reveal that the HMF formation is significantly reduced after blanching of bananas at 70 ºC for 45 min by 80.00% and 85.35% in Abu and Tanduk varieties, respectively (P<0.05).